Parental procreative obligation and the categorisation of disease: the case of cystic fibrosis - Bosslet, T. (Journal of medical ethics, 2011)
The advent of prenatal genetic diagnosis has sparked debates among ethicists and philosophers regarding parental responsibility towards potential offspring. Some have attempted to place moral obligations on parents to not bring about children with certain diseases in order to prevent harm to such children. There has been no rigorous evaluation of cystic fibrosis in this context. This paper will demonstrate cystic fibrosis to have unique properties that make it difficult to categorise among other diseases with the goal of promulgating a reproductive rule. Once this is established, it will be demonstrated that procreative rules that appeal to future health are inadequate in the era of advancing genetic knowledge. Utilising a specification of Joel Feinberg's ‘open future’ concept outlined by Matteo Mameli, it will offer an analysis of parental obligation that does not constrain parents of potential children with cystic fibrosis with a moral obligation not to bring them about.